2008
DOI: 10.1007/s00284-008-9137-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Role of Chemotaxis and Biofilm Formation as Requirements for Colonization of Roots and Seeds of Soybean Plants by Bacillus amyloliquefaciens BNM339

Abstract: This article correlates colonization with parameters, such as chemotaxis, biofilm formation, and bacterial growth, that are believed to be connected. We show here, by using two varieties of soybean plants that seeds axenically produced exudates, induced a chemotactic response in Bacillus amyloliquefaciens, whereas root exudates did not, even when the exudates, also collected under axenic conditions, were concentrated up to 200-fold. Root exudates did not support bacterial cell division, whereas seed exudates c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 36 publications
2
40
0
Order By: Relevance
“…Production of detectable quantities of IAA usually requires an exogenous source of tryptophan which, in the rhizosphere, is present in host root exudates (13,14,27,43,44,45,64,72,73). The addition of tryptophan to culture media induced ipdC expression in E. cloacae UW5 and in A. brasilense strain Sp7 (44,53,73), although the regulatory proteins that control tryptophan-mediated ipdC expression were not identified in these studies.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Production of detectable quantities of IAA usually requires an exogenous source of tryptophan which, in the rhizosphere, is present in host root exudates (13,14,27,43,44,45,64,72,73). The addition of tryptophan to culture media induced ipdC expression in E. cloacae UW5 and in A. brasilense strain Sp7 (44,53,73), although the regulatory proteins that control tryptophan-mediated ipdC expression were not identified in these studies.…”
mentioning
confidence: 80%
“…It has been shown that the expression of ipdC encoding indole-3-pyruvate decarboxylase, a key enzyme in the IAA biosynthetic pathway of some PGPRs, including E. cloacae UW5 and A. brasilense Sp7, is upregulated by tryptophan (44,53,73). In the rhizosphere, tryptophan is present in root exudates and from dead microorganisms and plant tissue (27,72), suggesting that a signal for upregulation of the indole-3-pyruvate pathway and, therefore, IAA production, in PGPR is present in the rhizosphere. Indeed, ipdC-driven reporter gene expression studies have shown that expression of ipdC in E. herbicola 299R is plant inducible.…”
Section: Vol 190 2008mentioning
confidence: 99%
“…This assay was adapted from Yaryura et al (38), as detailed in SI Materials and Methods. In brief, Zea mays seeds were surface-sterilized, germinated for 2 days in the dark, transferred to culture tubes containing 5 mL of mineral solution and filter paper as mechanical support of the seedling, and inoculated with equal amounts of wild-type and mutant cells.…”
mentioning
confidence: 99%
“…It appears likely that attraction to the root constitute the first step toward colonization for many rhizobacteria, since several studies show the chemoattraction of various PGPR such as P. fluorescens, Azospirillum spp., Azotobacter chroococcum and Bacillus species toward whole roots exudates or seed exudates (De Weert et al, 2002;Gafny, Okon, Kapulnik, & Fischer, 1986;Heinrich & Hess, 1985;Sood, 2003;Tan et al, 2013;Yaryura et al, 2008;Zheng & Sinclair, 1996). Root exudates are a complex blend of high and low molecular weight compounds, many of which can induce chemotactic response in PGPR (Bais, Broeckling, & Vivanco, 2008).…”
Section: Introductionmentioning
confidence: 99%